A Study on the Effects of Plug Shape on Operating Performance of an Electric Pressure Regulator Applied for Gaseous Fueled Vehicles - Nguyen, Ba Hung; Le, Anh Tuan; Lim, Ocktaeck (Smart Systems and Devices, 2021)
A model-based study was conducted to examine the effects of plug shape on electromagnetic force and dynamic response of an electric pressure regulator (EPR) applied for gaseous fueled vehicles. Mathematical models were established to describe the operation of the EPR, including mechanical and electrical models. A two-dimensional (2D) symmetric model of the EPR was built in Maxwell software to simulate the electromagnetic force under the effects of plug shape. Afterward, the 2D symmetric model of EPR with the electromagnetic force calculated was imported into Simplorer software to simulate the dynamic response of the EPR based on the influence of plug shape. The shape of plug in the EPR was changed through the dimension parameters denoted by dimension (h) and slope angle (a). The simulation results show that the electromagnetic force and dynamic response of the EPR can be optimized when h and a are selected at 3mm and 48°, respectively.